APPLICATION OF DECISION SUPPORT SYSTEM WITH SIMPLE ADDITIVE WEIGHTING METHOD TO DETERMINE STUDENT ACHIEVEMENTS AT SMA MAHATMA GADING JAKARTA - Maria Korsini; Ismailah Ismailah; Erlin Windia Ambarsari (BIOS: Jurnal Informatika dan Sains, 2023)
This study aims to determine outstanding students using a decision support system with the simple additive weighting method at SMA Mahatma Gading Jakarta. The research method used is descriptive qualitative, data collection with interviews, literature analysis and questionnaires. The calculation stages with the simple additive weight method consist of identifying criteria, normalization, weighting criteria and calculating final scores with four assessment criteria for outstanding students, namely academic grades, attendance, attitudes and non-academics. The results of the analysis obtained that the implementation of the decision support system with the simple additive weighting method ran well, indicated by giving a ranking to each alternative in determining outstanding students by looking at the ranking process carried out with the highest score results. The final result of the 3 (three) best rankings, namely Ardiansa Martawijaya got the first rank with a score of 0.921, then Revan Sahal got the second rank with a score of 0.902 and the third rank was a student named Owen Cornelius with a score of 0.893.